Light detection and ranging (LiDAR) and multispectral studies of disturbed Lake Superior coastal environments - W. Charles Kerfoot; Foad Yousef; Sarah A. Green; Robert Regis; Robert Shuchman; Colin N. Brooks; Mike Sayers; Bruce Sabol; Mark Graves (Limnology and Oceanography, 2012)
Due to its high spatial resolution and excellent water penetration, coastal light detection and ranging (LiDAR) coupled with multispectral imaging (MSS) has great promise for resolving shoreline features in the Great Lakes. Previous investigations in Lake Superior documented a metal‐rich “halo” around the Keweenaw Peninsula, related to past copper mining practices. Grand Traverse Bay on the Keweenaw Peninsula provides an excellent Great Lakes example of global mine discharges into coastal environments. For more than a century, waste rock migrating from shoreline tailings piles has moved along extensive stretches of coast, damming stream outlets, intercepting wetlands and recreational beaches, suppressing benthic invertebrate communities, and threatening critical fish breeding grounds. In the bay, the magnitude of the discarded wastes literally “reset the shoreline” and provided an intriguing field experiment in coastal erosion and spreading environmental effects. Employing a combination of historic aerial photography and LiDAR, we estimate the time course and mass of tailings eroded into the bay and the amount of copper that contributed to the metal‐rich halo. We also quantify underwater tailings spread across benthic substrates by using MSS imagery on spectral reflectance differences between tailings and natural sediment types, plus a depth‐correction algorithm (Lyzenga Method). We show that the coastal detail from LiDAR and MSS opens up numerous applications for ecological, ecosystem, and geological investigations.